Effectiveness of Genially interactive media in improving presentation competence of elementary school students - Rina Indrawaty; Euis Eti Rohaeti; Reka Yuda Mahardika (Himpunan Pengembang Kurikulum Indonesia, 2025)
Genially media, with all its advantages, is one of the reliable alternatives to address the challenges of modern education, particularly in creating innovative, enjoyable, and meaningful learning experiences for students. This study aims to measure the effectiveness of Genially interactive media in improving the presentation skills of fifth-grade elementary school students. The method used is quasi-experimental with a one-group pretest-posttest design. Participants consisted of 29 students selected through purposive sampling. Data were collected through presentation tests before (pretest) and after (posttest) the intervention using Genially over three sessions. Data analysis utilized the Shapiro-Wilk test for normality and the Wilcoxon Signed-Rank test to measure the significance of improvement. The results showed an average increase in presentation scores from 61.21 (pretest) to 84.48 (posttest) with significance at 0.001. These findings prove that Genially is effective in improving students' presentation competencies, supporting constructivism theory and multimedia-based learning. The implications of this study emphasize the importance of integrating digital media into the elementary school curriculum. Genially media not only serves as a learning aid but also as an effective tool in comprehensively improving presentation skills among elementary school students. Abstrak Media Genially dengan semua keunggulannya menjadi salah satu alternatif yang dapat diandalkan untuk menjawab tantangan pendidikan modern, khususnya dalam menciptakan pengalaman belajar yang inovatif, menyenangkan, dan bermakna bagi peserta didik. Penelitian ini bertujuan untuk mengukur efektivitas media interaktif Genially dalam meningkatkan kompetensi presentasi peserta didik kelas V Sekolah Dasar (SD). Metode yang digunakan adalah quasi-experimental dengan desain one group pretest-posttest. Partisipan terdiri dari 29 peserta didik yang dipilih secara purposif. Data dikumpulkan melalui tes presentasi sebelum (pretest) dan setelah (posttest) intervensi menggunakan Genially selama tiga pertemuan. Analisis data menggunakan uji Shapiro-Wilk untuk normalitas dan uji Wilcoxon Signed-Rank untuk mengukur signifikansi peningkatan. Hasil menunjukkan peningkatan rata-rata skor presentasi dari 61,21 (pretest) menjadi 84,48 (posttest) dengan signifikansi 0,001. Temuan ini membuktikan bahwa Genially efektif dalam meningkatkan kompetensi presentasi peserta didik, mendukung teori konstruktivisme dan pembelajaran berbasis multimedia. Implikasi penelitian ini menekankan pentingnya integrasi media digital dalam kurikulum sekolah dasar. Media Genially tidak hanya berperan sebagai alat bantu pembelajaran, tetapi juga sebagai sarana yang efektif dalam meningkatkan keterampilan presentasi secara menyeluruh pada peserta didik SD. Kata Kunci: Genially; kompetensi presentasi; media interaktif